Effect of flaxseed supplementation of dairy cows' forage on physicochemical characteristic of milk and Raclette cheese. (15th July 2015) - Bocquel, Dimitri; Marquis, Raphaël; Dromard, Michel; Salamin, Paul‐André; Rey‐Siggen, Janine; Héritier, Julien; Kosińska‐Cagnazzo, Agnieszka; Andlauer, Wilfried
Abstract : The composition of bovine milk depends on breed, lactation stage, age of cows and dietary factors. The effect of flaxseed supplementation of forage diet on the chemical composition of milk and the physicochemical and sensory characterisation of Raclette cheese were investigated in this study. As a result of diet supplementation, the proportion of saturated fatty acids in milk decreased and the content of α‐linolenic and oleic acids increased. Concerning the cheese samples, the hardness was significantly reduced due to the flaxseed supplementation, which can positively affect the quality of the cheese due to the diminished risk of crack formation. Sensory characteristics of melted Raclette cheese were not affected by the dietary treatments.